Power dynamics and water reform in the Zimbabwean context: implications for the poor - Mapedza, Everisto D.; Geheb, Kim (IWA Publishing, 2010)
In Zimbabwe, the state has been reconfiguring the water sector since 1998, as has been happening more generally within the wider Southern African region. Within the water sector, as in broader environmental governance, decentralization is increasingly being proposed as an important step towards increased accountability, equity and positive social and environmental outcomes. Decentralization is defined as the devolution of powers to local level institutions which are downwardly accountable to their constituencies. This paper looks at the Zimbabwean case of decentralising water management and assesses whether or not this process has yielded positive social, economic and environmental outcomes. The paper views the reform process as a reflection of the power asymmetries that work against the interests of poor households in accessing water for both domestic and productive uses.